2017
DOI: 10.1007/s00430-017-0505-2
|View full text |Cite
|
Sign up to set email alerts
|

Aspects on the history of transmission and favor of distribution of viruses by iatrogenic action: perhaps an example of a paradigm of the worldwide spread of HIV

Abstract: Transmission of infectious agents might be associated with iatrogenic actions of charitable help in health care. An example is the vaccination against yellow fever in USA that transmitted hepatitis B virus. Another example is injections of praziquantel for treatment and cure of schistosomiasis in Central and Northern Africa, with a focus in Egypt that has spread hepatitis C virus. There is no indication that human T-lymphotropic virus type 1 was spread by injection treatment for African trypanosomiasis, syphil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…HIV-1 is an enveloped retrovirus with two copies of an ssRNA genome, which enters the host primarily through mucosal surfaces, where it replicates after the integration of the newly retro-transcribed double-stranded DNA (dsDNA) [5,10,11]. Predominant routes of HIV-1 transmission include sexual contact, percutaneous (through contaminated needles and blood products), and perinatal [5,10,12]. Worldwide, about 90% of new HIV infections are attributed to sexual transmission, with most infected people being women [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…HIV-1 is an enveloped retrovirus with two copies of an ssRNA genome, which enters the host primarily through mucosal surfaces, where it replicates after the integration of the newly retro-transcribed double-stranded DNA (dsDNA) [5,10,11]. Predominant routes of HIV-1 transmission include sexual contact, percutaneous (through contaminated needles and blood products), and perinatal [5,10,12]. Worldwide, about 90% of new HIV infections are attributed to sexual transmission, with most infected people being women [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“… 45 , 46 The elucidation of the cross-species transmission dynamics has gained attention, as well as opened doors to exploring restriction factors and intrinsic immunity as additional paradigms. 47–49 …”
Section: Key Components: Armamentsmentioning
confidence: 99%
“…45,46 The elucidation of the crossspecies transmission dynamics has gained attention, as well as opened doors to exploring restriction factors and intrinsic immunity as additional paradigms. [47][48][49] Viral Transmission: Deployment SARS-CoV-2 is a respiratory virus, primarily spread from person to person through respiratory droplets containing viral particles. A study reported finding viable SARS-CoV -2 virus even after 72 hours on plastic or stainless-steel surfaces, although titer was reduced from 10 3.7 to 10 0.6 TCID 50 (1259-fold reduction) for both.…”
mentioning
confidence: 99%
“…Syndemic interactions may act in several ways and take place at different levels. For instance, even medical treatments can occasionally generate iatrogenic syndemics: Hepatitis B and C infections were spread involuntarily during yellow fever vaccine campaigns and mass intravenous drug administration against schistosomiasis in USA and Egypt, respectively [ 10 , 11 , 12 ]; besides, drugs to treat one disease may undermine treatments given for other reasons (such as detrimental DDIs between some antiretroviral and anti-tuberculosis drugs).…”
Section: Introductionmentioning
confidence: 99%
“…While in the past, malaria was one of the most important determinants of pathocoenosis, due to its impact on populations’ mortality and morbidity, and to its synergism with other diseases [ 6 , 8 ], HIV infection powerfully emerged in the last century. It has been hypothesised that the initial spread of the HIV pandemic in sub-Saharan Africa was likely eased by industrial evolution as well as by successful vaccine campaigns among tropical countries in the early twentieth century [ 11 , 13 ]. The HIV pandemic is a lifelong process closely entwined with unquantifiable opportunistic and non-opportunistic co-infections, non-communicable diseases, polypharmacy, poverty, marginalisation, gender inequality, malnutrition, and stigma.…”
Section: Introductionmentioning
confidence: 99%